Pyrogenic Carbon Erosion: Implications for Stock and Persistence of Pyrogenic Carbon in Soil - Abney, Rebecca B.; Berhe, Asmeret Asefaw (Frontiers in Earth Science, 2018)
Pyrogenic carbon (PyC) constitutes an important pool of soil organic matter, particularly for its reactivity and because of its assumed long residence times in soil. In the past, research on the dynamics of PyC in the soil system has focused on quantifying stock and mean residence time of PyC in soil, as well as determining both PyC stabilization mechanisms and loss pathways. Much of this research has focused on decomposition as the most important loss pathway for PyC from soil. However, the low density of PyC and its high concentration on the soil surface after fire indicates that a significant proportion of PyC formed or deposited on the soil surface is likely laterally transported away from the site of production by wind and water erosion. Here, we present a synthesis of available data and literature to compare the magnitude of the water-driven erosional PyC flux with other important loss pathways, including leaching and decomposition, of PyC from soil. Furthermore, we use a simple first-order kinetic model of soil PyC dynamics to assess the effect of erosion and deposition on residence time of PyC in eroding landscapes. Current reports of PyC mean residence time (MRT) range from 250 to 660 years. Using a specific example-based model system, we find that ignoring the role of erosion may lead to the under- or over-estimation of PyC MRT on the centennial time scale. Furthermore, we find that, depending on the specific landform positions, timescales considered, and initial concentrations of PyC in soil, ignoring the role of erosion in distributing PyC across a landscape can lead to discrepancies in PyC concentrations on the order of several hundred g PyC m-2. Erosion is an important PyC flux that can act as a significant control on the stock and residence time of PyC in the soil system.